MANAJEMEN PROGRAM PELATIHAN SENI TRADISIONAL PADA SANGGAR SENI SEKAR WIJAYA KUSUMA SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT - - Pujiwiyana (Imaji, 2012)
The construction of traditional art in society may function as: a religious, educative and social integration enforcer, entertainment, and occupation. Thus, the activity of traditional art construction is also an effort of society outsourcing. For achieving this purpose it needs the implementation of a strategic program management. By the implementation of this program hopefully the entire activity of art construction in traditional gallery can be designed and conducted appropriately. In so doing, the entire program can be evaluated kindly, and the result of activity can be quantified. If all this is achieved, traditional art can be a focal point for social interaction, society involvement and wide-based participation and becomes an important process in society outsourcing in social, economic and political fields.